Performance Characterization of a Switchable Acoustic Resolution and Optical Resolution Photoacoustic Microscopy System - Moothanchery, Mohesh (2017)
Photoacoustic microscopy (PAM) is a scalable bioimaging modality; one can choose low acoustic resolution with deep penetration depth or high optical resolution with shallow imaging depth. High spatial resolution and deep penetration depth is rather difficult to achieve using a single system. Here we report a switchable acoustic resolution and optical resolution photoacoustic microscopy (AR-OR-PAM) system in a single imaging system capable of both high resolution and low resolution on the same sample. Lateral resolution of 4.2 µm (with ~1.4 mm imaging depth) and lateral resolution of 45 μm (with ~7.6 mm imaging depth) was successfully demonstrated using a switchable system. In vivo blood vasculature imaging was also performed for its biological application.